Phytochemical studies and bioactivity evaluation (DENV-2 NS2B/NS3 protease) of Beilschmiedia glabra and Endiandra kingiana (Lauraceae) / Syazreen Nadia Sulaiman - Syazreen Nadia , Sulaiman (2019)
Preliminary survey of the dichloromethane crude extracts of two Lauraceae species (Beilschmiedia glabra and Endiandra kingiana) showed moderate dengue inhibition against dengue type 2 NS2B/NS3 protease with percentage of inhibition by 51.28 ± 13.9% and 65.05 ± 3.7%, respectively. Isolation and purification on the active extracts of the B. glabra and E. kingiana yielded seventeen compounds. B. glabra gave nine compounds; 123, 124, 125, 126, 127, 128, 129, 130, and 131. Among nine compounds, 130, and 131 were identified as new neolignans which features a rare oxetane moiety in the structure. Meanwhile, E. kingiana afforded eight compounds; 132, 133, 134, 135, 136, 137, 138 and 139, with 136 identified as a new benzofuran. Their structures were elucidated by spectroscopic techniques such as 1D and 2D NMR, UV, IR, LCMS-IT-TOF and comparison with the literature values. All isolated compounds which of had sufficient amount were tested for inhibitory activity against dengue type 2 NS2B/NS3 protease. From B. glabra, two compounds, 125 and 130 were tested which showed weak inhibition with percentage inhibition less than 50% towards the dengue type 2 NS2B/NS3 protease. As for E. kingiana, five compounds, 134, 135, 136, 137, and 138 were also subjected to in vitro test against NS2B/NS3 protease of DENV-2 where 136 (61.23 ± 7.0%), 137 (69.93 ± 3.3%), and 138 (62.02 ± 6.2%) showed moderate activity with percentage inhibition more than 50%, while the remaining two compounds showed weak inhibition. Therefore, three compounds (136, 137 and 138) with percentage of inhibition more than 50%; were further evaluated in order to determine their respective IC50 values. Compound 137 had a higher potency with a lower IC50 value compared to the other active compounds towards the protease. Then these three active compounds, 136 (IC50 = 403.14 ± 33.03), 137 (IC50 = 170.10 ± 5.94), and 138 (IC50 = 184.13 ± 2.11) were subjected to molecular docking studies to provide much clear picture of the site at which the active compounds bind to the protease. Based on molecular docking studies, 136, 137, and 138 showed common hydrogen bonding interactions with the oxygen atom in each compound with Asn152 at S2 pocket of DENV-2 NS2B/NS3 protease. However, that was the only similar interactions between these three active compounds. For compound 137 and 138, both showed similar interaction with Asp129 and Tyr161 of the DENV-2 NS2B/NS3 protease at S1 pocket, however with different type of bonding as 137 having hydrogen bonding while 138 having